2016
DOI: 10.1186/s12894-016-0154-6
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of XP11.2 translocation/TFE3 gene fusion renal cell carcinoma: a systematic review and meta-analysis of observational studies

Abstract: BackgroundRenal cell carcinoma (RCC) associated with Xp11.2 translocation/TFE3 gene fusion (Xp11.2 RCC) is a rare subtype of RCC which is firstly described as a distinct entity in 2004 so that clinical characteristics of Xp11.2 RCC in different gender and age are unknown. The purpose of systematic review and meta-analysis is to provide a comprehensive assessment on them.MethodsMEDLINE, EMBASE and Cochrane databases were searched for studies which evaluate the clinical characteristics of Xp11.2 RCC. The literat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
31
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 33 publications
3
31
3
Order By: Relevance
“…This result was consistent with another Asian cohort [5] (0.72% in Korea) which further demonstrated the rarity of this disease in adults. Although a prior meta-analysis suggested a female gender predominance in adult XP11.2 translocation RCC [13] , possibly due to its X-chromosome related nature, our study found an equal gender distribution as observed in children which might be explained by the absence of translocation on the Barr body (inactive X chromosome) or by the relatively small number of patients enrolled. Moreover, consistent with previous reports [7,18] and for unknown reasons, right side prevalence was observed in our cohort.…”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…This result was consistent with another Asian cohort [5] (0.72% in Korea) which further demonstrated the rarity of this disease in adults. Although a prior meta-analysis suggested a female gender predominance in adult XP11.2 translocation RCC [13] , possibly due to its X-chromosome related nature, our study found an equal gender distribution as observed in children which might be explained by the absence of translocation on the Barr body (inactive X chromosome) or by the relatively small number of patients enrolled. Moreover, consistent with previous reports [7,18] and for unknown reasons, right side prevalence was observed in our cohort.…”
Section: Discussioncontrasting
confidence: 85%
“…XP11.2 translocation RCC accounts for 20-40% of pediatric RCC [13] and only 0.72-1.6% of adult RCC [5,14] . This subtype of RCC in adults requires special attention and more intensive researches for its rarity, aggressiveness in nature [3,13] and possible different treatment options (eg. m-TOR inhibitors or VEGFtargeted agents) [16,17] .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, our study inferred that the incidence of female Xp11 translocation RCCs in the adult group was significantly higher than that in the male group, as it is a rare malignant tumour in the urinary system with a higher incidence in females. Meta-analysis confirmed that females were more predominant than males in adult patients, while in children, no sex-related predominance was observed 13 . However, further exploration is still essential to understand why there is an age-related difference in incidence and a high incidence in adult female patients.…”
Section: Discussionmentioning
confidence: 72%
“…In addition, the natural history of the disease is variable between children and adults based on clinical experience. Meta-analysis showed that clinical characteristics between children and adults were distinctive, including the incidence of lymphatic metastases, tumour stage and prognosis 13 . In view of the lack of a large sample size and longer follow-up for this relatively recent category of tumours, we grouped five urological cancer research institutes together to compare the clinicopathologic features and outcomes in patients with paediatric and adult Xp11 translocation RCCs.…”
mentioning
confidence: 99%
“…XP11.2 RCC accounts for 20 -40% of pediatric RCC [13] and only 0.72-1.6% of adult RCC [5,14] . This subtype of RCC in adults requires special attention and more intensive researches for its rarity, aggressiveness in nature [3,13] and possible different treatment options (eg. m-TOR inhibitors or VEGFtargeted agents) [16,17] .…”
Section: Discussionmentioning
confidence: 99%